2008
DOI: 10.1038/ejhg.2008.175
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in mammalian tolloid-like 1 gene detected in adult patients with ASD

Abstract: Atrial septal defect (ASD) is an incomplete septation of atria in human heart causing circulatory problems. Its frequency is estimated at one per 10 000. Actions of numerous genes have been linked to heart development. However, no single gene defect causing ASD has yet been identified. Incomplete heart septation similar to ASD was reported in transgenic mice with both inactive alleles of gene encoding mammalian zinc metalloprotease a mammalian tolloid-like 1 (tll1). Here, we have screened 19 ASD patients and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…After 10 dpc, mTLL1 is more broadly expressed, but mTLL1-null mice die at ϳ13.5 dpc from deficits apparently confined to the cardiovascular system (30). In humans, non-synonymous polymorphisms have been reported in mTLL1 coding sequences in several patients with atrial septal defects (36), although the significance of these findings remains to be determined.…”
Section: B/tp Distributions and General Functionsmentioning
confidence: 95%
“…After 10 dpc, mTLL1 is more broadly expressed, but mTLL1-null mice die at ϳ13.5 dpc from deficits apparently confined to the cardiovascular system (30). In humans, non-synonymous polymorphisms have been reported in mTLL1 coding sequences in several patients with atrial septal defects (36), although the significance of these findings remains to be determined.…”
Section: B/tp Distributions and General Functionsmentioning
confidence: 95%
“…However, this child also had a de novo 17q deletion that was considered pathogenic. The deleted region on 4q32 harbors the TLL1 gene, in which heterozygous mutations have been associated with atrial septal defects, 22 and large deletions of 4q have also been reported in association with congenital heart defects. 23 Because the father was already aware of this deletion, the variant was reported.…”
Section: Variants Of Uncertain Significancementioning
confidence: 99%
“…TLL1 encodes the astacin-like, zinc-dependent, metalloprotease Tolloid-like protein 1, a gene in which mutations have previously been identified in sporadic cases of ASD. 24 An A to G transition at nucleotide position 787 that predicted an amino acid change from an isoleucine to a valine at residue 263 (TLL1 Ile263Val, NM_001204760) was identified in an affected member (II-1) and not in an unaffected member, II-6 (Figure 2A–D). This mutation causes an amino acid change that occurs at a highly conserved residue in the metalloprotease active domain, which is required for TLL1’s protease activity (Figure 2E and 2F, Supplemental Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…41 TLL1 has not been that well studied in human CHD, but heterozygous mutations have been reported in patients with ASD. 24 The Ile263Val (I263V) variant identified in TLL1 is considered likely pathogenic based on several lines of evidence. It was identified in the only available affected individual and not in one unaffected individual in family D. It is very rare in the general population, identified in only 1 out of 60,650 individuals in the ExAC database, and is predicted to be pathogenic by bioinformatic analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation